PENGARUH MOTIVASI, KEPUASAN DAN SIKAP KERJA TERHADAP KINERJA KARYAWAN KANTOR KECAMATAN KLOJEN DAN LOWOKWARU KOTA MALANG - Nurhasna Sa’ban; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTTo find out a description of work motivation, job satisfaction, work attitude and employee performance at the Klojen District Office and Lowokwaru District, Malang City. The population and sample were employees of the Klojen District Office and Lowokwaru District Malang City were 67 people. Data collection through questionnaires. The analysis in this study used SPSS version 20. The sampling technique used saturated sampling and testing data used in this study included descriptive statistics, validity test, reliability test, normality test, classic assumption test, multiple linear regression test and research hypothesis testing.Keywords: Motivation, Satisfaction, Work Attitude, and Employee Performance